Cuestiones sobre la prueba en el proceso contencioso administrativo español - Cordón Moreno, Faustino (Revista de Derecho, 2019)
The article is a specialized work with targets the problem of evidence in the processing of an administrative litigation process in Spain. The need for this study arises from the diverse functions which, in evidential material, the different Spanish laws have been granting to the administrative litigation Judge. For it each of the evidential activities which are conducted throughout an administrative litigation process are analyzed and the main problems originated in those activities such as remission norms, the application of burden of proof in terms of the application of the presumption of legality in administrative acts, the criteria for rating of evidence, etc. are studied.
Keywords: Evidence; administrative litigation; burden of proof; presumption of legality; presumption of veracity